Elementary and Intermediate Algebra: Concepts & Applications (6th Edition)

Published by Pearson
ISBN 10: 0-32184-874-8
ISBN 13: 978-0-32184-874-1

Chapter 4 - Polynomials - Study Summary - Practice Exercises - Page 296: 22



Work Step by Step

Subtract each term to obtain: $(9x^2-3x)-(4x-x^2) \\=9x^2-3x-4x-(-x^2) \\=9x^2-3x-4x+x^2$ Combine like terms to obtain: $=(9x^2+x^2)+(-3x-4x) \\=(9+1)x^2+(-3-4)x \\=10x^2+(-7x) \\=10x^2-7x$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.